Soil physical quality as quantified by S index under different management system in rice-wheat system - SINHA, NISHANT K.; CHOPRA, USHA KIRAN; SINGH, ANIL KUMAR; KUMAR, NIRMAL; MOHANTY, MANORANJAN; SOMASUNDARAM, J. (Journal of Soil and Water Conservation, 2020)
Soil physical quality is one of the three important aspects of soil quality, besides biological and chemical quality. Decline in soil physical quality may have serious consequences on biological and chemical properties thereby making it relevant to study soil physical quality for maintaining soil health in long run. In this investigation, Dexter S theory was applied to evaluate the soil physical environment under different tillage and nutrient treatments in rice-wheat (R-W) system. Two tillage treatments viz. puddling and direct sowing and nine nutrient treatments viz. (i) T1- Control (No fertilizer + crop), (ii) T2- 100% recommended dose of nitrogen (N), phosphorous (P) and potassium (K), (iii) T3- 100% NPK (25% N substituted by farmyard manure (FYM)), (iv) T4- 100% NPK+ green manure (Sesbania), (v) T5- 100% NPK (25% N substituted by biofertilizer), (vi) T6- 100% NPK (25% N substituted by sewage sludge), (vii) T7 - 100% NPK+ crop residue (from previous crop), (viii) T8- 100% organic source (50% FYM + 25% biofertilizer+ 25% crop residue), and (ix) T9- Blank plot; were identified for this study. The soil physical environment significantly improves under the direct sowing when compared to puddled soil. Within nutrient treatments, value of S index was highest in T4 whereas lowest was observed in T1. There is high and significant correlation observed between S index, soil physical parameter and crop yield which shows that S index can be used for quantifying soil physical quality under diverse environments.